Information Technology in Teaching and Learning French as a Foreign Language at the University of Jordan - Emaish, Nahed (European Scientific Journal, ESJ, 2016)
This research aims to investigate to what extent students and professors at the University of Jordan use information technology in teaching and learning French. It also intends to evaluate the effect that IT tools have on the teaching/learning of this language at the Department of French at this university. The study sample was confined to (90) third-year students majoring in French. Another sample included all (8) professors in the department. The research method utilized two questionnaires, one for the professors and the other for students. The data was analyzed by descriptive statistics, and highlighting means and frequencies. The findings revealed that technology is used by the majority of students for such tasks as using online dictionaries, getting information for their projects and assignments and doing power point presentations. These activities play a part in developing their learning of the language. The findings also showed limitations in their interaction with native-speakers, use of social media, movies, and songs in the target language. As for the professors, the answers revealed that information technology is not often used in their courses. And when used, it is limited to e-mails or power-point presentations.